A DEM model for visualising damage evolution and predicting failure envelope of composite laminae under biaxial loads. (1st October 2016) - Ismail, Yaser; Yang, Dongmin; Ye, Jianqiao
Abstract: A two dimensional particle model based on the discrete element method (DEM) is developed for micromechanical modelling of fibre reinforced polymer (FRP) composite laminae under biaxial transverse loads. Random fibre distribution within a representative volume element (RVE) is considered for the micromechanical DEM simulations. In addition to predicting the stress-strain curves of the RVEs subjected to transverse compression and transverse shear stresses against the experimental testing results and other numerical modelling results, the DEM model is also able to capture the initiation and propagation of all micro damage events. Fibre distribution is found to more significantly influence the ultimate failure of composite laminae under transverse shear, while it has much less effect on the failure under transverse compression. The failure envelope of composite laminae under biaxial transverse compression and transverse shear is predicted and compared with Hashin and Puck failure criteria, showing a reasonable agreement. The predicted failure envelope is correlated with the damage evolution and the quantitative analysis of failure events, which improves the understanding of the failure mechanisms.